Construction of a Video Transmission Scenario in Software-Defined Networks for QoE Estimation - Quizza-Hernández, Vicko; Arango-Colorado, Juan-Camilo; Campo-Muñoz, Wilmar-Yesid (Universidad Pedagógica y Tecnológica de Colombia, 2022)
The services supported by data networks have become widespread, so the architectures of the new data networks are service-oriented. They are endowed with intelligence, flexibility, and programmability. The preceding is with the aim of providing acceptability by users. Thus, this paper presents the construction of a video transmission scenario over a software-defined network (SDN, Software-Defined Networking) using free software and modifying its behavior with background traffic, on which the Quality of Experience (QoE) is estimated. Subjective and objective metrics were used for the QoE estimation. For the first one, the Mean Opinion Score (MOS) was used, while the second one was studied with the Full Reference Image Quality Assessment (FR-IQA). Finally, a correlation between the two types of metrics was proposed.